Legal Review Concerning Amputed Authority of DPR and DPD in The Process of Regional Propagation in Indonesia - L. M Ricard Zeldi Putra; Indah Kusuma Dewi; Ernawati Ernawati; Waode Novita Ayu Muthmainna; Mashendra Mashendra; Jayanto Jayanto (Lembaga Penelitian dan Pengabdian Masyarakat, 2022)
Article 38 Paragraph (1) of Law No. 23 of 2014 concerning Local Government as amended by Law No. 9 of 2015 concerning the second Amendment to Law No. 23 of 2014 concerning Local Government is contrary to Article 20A Paragraph (1), Article 21 and Article 22D paragraph (1) of the 1945 Constitution. Where the proposal for regional expansion proposed by Governor is takeover of authority. In the 1945 Constitution has been regulated in a limitative manner the authority given to the DPR and DPD institutionally the power to form the law and give authority to the President to submit a draft law. Author examines legal analysis of the authority of the DPR and DPD in the process of regional expansion. Type of research is normative research and qualitative descriptive form. The authority of the DPR and DPD in the process of regional expansion as regulated has been constitutionally harmed, namely the right to submit a draft law related to regional expansion and participate together to discuss the draft law which results in the process of regional expansion cannot be submitted by the DPR and DPD which has a legislative function.